2000
DOI: 10.1038/sj.ejcn.1600894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an oleic acid enriched-diet vs NCEP-I diet on LDL susceptibility to oxidative modifications

Abstract: Objective: The objective of this trial was to compare the effect on the susceptibility of plasma Low Density Lipoprotein (LDL) to oxidative modi®cations of consumption of two oleic rich diets, prepared with two different plant oils, virgin olive oil (OL) 1 and re®ned high monounsaturated fatty acids (MUFA sun¯ower oil (SU)), with the susceptibility of plasma LDL to oxidation after an National Cholesterol Education Program step 1 (NCEP-I) phase diet. Design: A randomized crossover design. Subjects and intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…Of the 14 studies referred to [38], only in two of them did MUFA -rich diets not promote a higher resistance of LDL to oxidation than PUFA-rich ones. Compared with high carbohydrate/low fat diets, the MUFA ones had a better effect [39,40], or a comparable one [41], on the susceptibility of the LDL to oxidation. We must point out that in most studies, the measured parameter was the susceptibility of isolated LDL to oxidation, an in vitro test, in which the characteristics of diene formation in LDL after oxidation with copper of the lipoprotein are measured [42].…”
Section: Lipid Oxidative Damagementioning
confidence: 89%
“…Of the 14 studies referred to [38], only in two of them did MUFA -rich diets not promote a higher resistance of LDL to oxidation than PUFA-rich ones. Compared with high carbohydrate/low fat diets, the MUFA ones had a better effect [39,40], or a comparable one [41], on the susceptibility of the LDL to oxidation. We must point out that in most studies, the measured parameter was the susceptibility of isolated LDL to oxidation, an in vitro test, in which the characteristics of diene formation in LDL after oxidation with copper of the lipoprotein are measured [42].…”
Section: Lipid Oxidative Damagementioning
confidence: 89%
“…Ainsi, selon Carmena et al [11], il existerait un défaut de protection vis-à-vis de l'oxydation des LDL lorsque le régime à base d'huile d'olive est à plus de 20 % de mono-insaturés par comparaison avec un régime plus équilibré. De plus, pour des régimes de même teneur en acide oléique mais de sources différentes (olive et tournesol oléique), Jimenez et Castro [20] viennent de vérifier qu'à représentation identique des acides gras mono-insaturés dans les LDL, la protection de ces lipoprotéines vis-à-vis de l'oxydation serait meilleure après le régime tournesol oléique, parce que positivement corrélé à l'enrichissement en alpha-tocophérol de ces LDL ; la haute teneur en tocophérols du tournesol oléique serait la source de cet enrichissement en alpha-tocophérol plasmatique.…”
Section: Le Processus Oxydatifunclassified
“…Five interventional studies showed beneficial effects of Mediterranean diet on TG concentrations (Shai et al, 2008;Esposito et al, 2004;Estruch et al, 2006;Esposito et al, 2009;Elhayany et al, 2011), whereas other studies did not find significant differences (de Lorgeril et al, 1994;Castro et al, 2000;Michalsen et al, 2006).…”
Section: Mediterranean Diet and Lipid Metabolismmentioning
confidence: 99%